Some like it cold: microbial transformations of mercury in polar regions - Barkay, Tamar; Kroer, Niels; Poulain, Alexandre J (Polar Research, 2011)
The contamination of polar regions with mercury that is transported from lower latitudes as inorganic mercury has resulted in the accumulation of methylmercury (MeHg) in food chains, risking the health of humans and wildlife. While production of MeHg has been documented in polar marine and terrestrial environments, little is known about the responsible transformations and transport pathways and the processes that control them. We posit that as in temperate environments, microbial transformations play a key role in mercury geochemical cycling in polar regions by: (1) methylating mercury by one of four proposed pathways, some not previously described; (2) degrading MeHg by activities of mercury resistant and other bacteria; and (3) carrying out redox transformations that control the supply of the mercuric ion, the substrate of methylation reactions. Recent analyses have identified a high potential for mercury-resistant microbes that express the enzyme mercuric reductase to affect the production of gaseous elemental mercury when and where daylight is limited. The integration of microbially mediated processes in the paradigms that describe mercury geochemical cycling is therefore of high priority especially in light of concerns regarding the effect of global warming and permafrost thawing on input of MeHg to polar regions. Keywords: Microbiology; mercury biogeochemistry; redox transformations; polar regions; methylation
Keywords: Antarktis; biogeokjemi; forurensning; mikrobiologi; miljøvern; polarområdene; økosystemer

Variability of nutrient and thermal structure in surface waters between New Zealand and Antarctica, October 2004-January 2005 - Campanelli, Alessandra; Massolo, Serena; Grilli, Federica; Marini, Mauro; Paschini, Elio; Rivaro, Paola; Artegiani, Antonio; Jacobs, Stanley S (Polar Research, 2011)
We describe the upper ocean thermal structure and surface nutrient concentrations between New Zealand and Antarctica along five transects that cross the Subantarctic Front, the Polar Front and the southern Antarctic Circumpolar Current front. The surface water thermal structure is coupled with variations in surface nutrient concentrations, making water masses identifiable by both temperature and nutrient ranges. In particular, a strong latitudinal gradient in orthosilicate concentration is centred at the Polar Front. On the earlier sections, which extend south-west from the Campbell Plateau, orthosilicate increases sharply southward from 10-15 to 50-55µmol l-1, between 58°S and 60°S, while surface temperature drops from 7°C to 2°C. Nitrate increases more regularly toward the south, with concentrations ranging from 10-12µmol l-1 at 54°S to 25-30µmol l-1 at 66°S. The same features are observed during the later transects between New Zealand and the Ross Sea, but the sharp silica and surface temperature gradients are shifted between 60°S and 64°S. Both temporal and spatial factors may influence the observed variability. The January transect suggests an uptake of silica, orthophosphate and nitrate between 63°S and 70°S over the intervening month, with an average depletion near 37%, 44% and 29%, respectively. An N/P apparent drawdown ratio of 8.8±4.1 and an Si/N apparent drawdown ratio >1 suggests this depletion results from a seasonal diatom bloom. A southward movement of the oceanic fronts between New Zealand and the Ross Sea relative to prior measurements is consistent with reports of recent warming and changes in the Antarctic Circumpolar Current. Keywords: Southern Ocean, nutrients, silica belt, Antarctic Circumpolar Current, expendable bathythermograph.
Keywords: Rosshavet; Sørishavet; fytoplankton; havstrømmer; næringsstoff; vannmasser; økosystemer

Global southern limit of flowering plants and moss peat accumulation - Convey, Peter; Hopkins, David W; Roberts, Stephen J; Tyler, Andrew N (Polar Research, 2011)
The ecosystems of the western Antarctic Peninsula, experiencing amongst the most rapid trends of regional climate warming worldwide, are important “early warning” indicators for responses expected in more complex systems elsewhere. Central among responses attributed to this regional warming are widely reported population and range expansions of the two native Antarctic flowering plants, Deschampsia antarctica and Colobanthus quitensis. However, confirmation of the predictions of range expansion requires baseline knowledge of species distributions. We report a significant southwards and westwards extension of the known natural distributions of both plant species in this region, along with several range extensions in an unusual moss community, based on new survey work in a previously unexamined and un-named low altitude peninsula at 69º22.0’S 71º50.7’W in Lazarev Bay, north-west Alexander Island, southern Antarctic Peninsula. These plant species therefore have a significantly larger natural range in the Antarctic than previously thought. This site provides a potentially important monitoring location near the southern boundary of the region currently demonstrated to be under the influence of rapidly changing climate trends. Combined radiocarbon and lead isotope radiometric dating suggests that this location was most likely deglaciated sufficiently to allow peat to start accumulating towards the end of the 19th century, which we tentatively link to a phase of post-1870 climate amelioration. We conclude that the establishment of vegetation in this location is unlikely to be linked to the rapid regional warming trends recorded along the Antarctic Peninsula since the mid-20th century. Antarctic plants, distribution limits, peat accumulation, dating.
Keywords: Antarktis; hårgress; klimaendringer; perleurt; planter; økosystemer

Spatial modelling of wetness for the Antarctic Dry Valleys - Stichbury, Glen; Brabyn, Lars; Green, T G Allan; Cary, Craig (Polar Research, 2011)
This paper describes a method used to model relative wetness for part of the Antarctic Dry Valleys using Geographic Information Systems (GIS) and remote sensing. The model produces a relative index of liquid water availability using variables that influence the volume and distribution of water. Remote sensing using Moderate Resolution Imaging Spectroradiometer (MODIS) images collected over four years is used to calculate an average index of snow cover and this is combined with other water sources such as glaciers and lakes. This water source model is then used to weight a hydrological flow accumulation model that uses slope derived from Light Detection and Ranging (LIDAR) elevation data. The resulting wetness index is validated using three-dimensional visualization and a comparison with a high-resolution Advanced Land Observing Satellite image that shows drainage channels. This research demonstrates that it is possible to produce a wetness model of Antarctica using data that are becoming widely available. Keywords: GIS; water; Antarctica; remote sensing.
Keywords: Antarktis; geografi; hydrologi; innsjø; isbreer; satellitt bilder; snø; vann; økosystemer